The Influence of MTHFR C677T Variants on Neuropathy Risk Among T2dm Patients Receiving Monotherapy Metformin - Michael Resta Surya Yanuar; Enade Perdana Istyastono; Dita Maria Virginia (Indonesian Journal of Pharmacy, 2024)
Neuropathy is the most common microvascular complication among type 2 diabetes mellitus (T2DM). Metformin consumption increases neuropathy risk. The Methylenetetrahydrofolate reductase (MTHFR) enzyme has confirmed its role in neuropathy. Metformin and MTHFR could decrease folate and induce hyperhomoscysteine. One of the common variants of the MTHFR gene is C677T and its located in the exon area. This study aimed to observe the association between variant C677T in the MTHFR gene and the risk of neuropathy among newly diagnosed T2DM patients with naive metformin. This cross-sectional study recruited 103 patients. The neuropathy risk was examined according to medical judgment through Neuropathy Symptom Score (NSS) and Neuropathy Disability Score (NDS) criteria. Genotyping C677T was performed using PCR-RFLP. This study found only one patient has a homozygote mutant, but more than 50% of patients were detected with allele mutants. There were no statistical differences in patient characteristics between CC and CT genotypes (p>0.05). Association between C677T and neuropathy risk was not significant statistically, either in the genotype model (p=0.97), allele model (p=0.82), and dominant model (p=0.91). There was still no significant association after adjusting for several confounding factors. We conclude that C677T in our population did not influence neuropathy risk. More specific criteria and laboratory parameters indicated neuropathy should be examined in the future study.Keywords: MTHFR, neuropathy, metformin, and T2DM